Integrated Analysis of the Prognosis-Associated RNA-Binding Protein Genes and Candidate Drugs in Renal Papillary Cell Carcinoma - Jiang, Silin; Ren, Xiaohan; Liu, Shouyong; Lu, Zhongwen; Xu, Aiming; Qin, Chao; Wang, Zengjun (Frontiers in Genetics, 2021)
RNA-binding proteins (RBPs) are considered playing significant roles in various cancer types. However, the functions of RBPs have not been clarified in renal papillary cell carcinoma (KIRP). In this study, we identified 31 downregulated and 89 upregulated differentially expressed RBPs based on the TCGA database and performed functional enrichment analyses. Subsequently, through univariate Cox, Random survival forests and multivariate Cox regression analysis, six RBPs of SNRPN, RRS1, INTS8, RBPMS2, IGF2BP3 and PIH1D2 were screened out and prognostic model was then established. Further analyses revealed that the high-risk group had the poor overall survival. The area under the curve (AUC) values were 0.87 and 0.75 at 3 years as well as 0.78 and 0.69 at 5 years in the training set and test set. We then plotted a nomogram based on six RBPs and tumor stage with the substantiation in the TCGA cohort. Moreover, we selected two intersectant RBPs and evaluate their biological effects by GSEA and predicted three drugs including STOCK1N-28457, pyrimethamine and trapidil by using the Connectivity Map. In summary, our research provides a novel insight into KIRP and aids the determination of prognosis as well as individualized therapeutic strategies.